The Role of Self-Adjustment in Self-Regulated Learning: A Correlational Study of Migrant University Students - Hasbi Rismi; Anissa Lestari Kadiyono; Diana Harding (Universitas PGRI Yogyakarta, 2026)
Educational migration in Indonesia is driven by disparities in the distribution of high-quality higher education institutions, but the specific mechanisms by which students from outside Java adjust to self-regulated learning (SRL) in the Indonesian context, which is fraught with pressure and collectivist norms, have not been explored in depth. This study aims to examine the role of adjustment to self-regulated learning among students from outside Java Island with a sample size (N=160) using a correlational design. The research instrument was developed based on Schneider’s and Zimmerman's theory, validated through Confirmatory Factor Analysis (CFA) and McDonald's Omega (ω) reliability test. Given the abnormal data distribution based on the Shapiro-Wilk test, statistical analysis used Spearman's Rho non-parametric technique. The findings showed a significant positive relationship between the two variables (ρ = 0.470, p < 0.001) with a coefficient of determination (R2) of 0.221. These results indicate that self-adjustment accounts for 22.1% of the variation in self-regulated learning, making it an important predictor but not the only factor. The remaining variance of 77.9% indicates the need for a multifactorial approach that considers social support and self-efficacy. The practical implications of this study emphasize the urgency of holistic counseling services in universities to strengthen migrant students’ emotional stability as the foundation for independent learning. Keywords: migrant university students, self-adjustment, self-regulated learning